FUNDAMENTAL PERTUMBUHAN PEREKONOMIAN DI INDONESIA - Prasetio Ariwibowo (JABE (Journal of Applied Business and Economic), 2016)
This research aims to determine the effect of the good and bad sides of the factors that affect the growth of the Indonesian economy, analyzing the fundamentals of  economic growth in Indonesia, and formulate strategic recommendations to improve the economy of Indonesia in the future.In the middle of the advancement of the economy in a country, the more the amount of money and goods / services that are circulating in the country. Society has a wide range of economic activities in the conduct of the circulation of money and goods in the form of production, consumption, distribution, and other economic activities in the form of buying and selling foreign currency, export and import activities, as well as the company's stock transactions at home and abroad. Recent developments in the world and domestic economic conditions pose challenges to maintaining the stability of economic growth in Indonesia. This research uses qualitative descriptive analysis focused on the fundamental strategy of growth of the Indonesian economy by purposive sampling and literature study of statistics at the Ministry of Finance, the Central Bureau of Statistics, and the Ministry of Trade of the Republic of Indonesia in 2013 - 2015 as the primary and secondary data.From these results it can be seen that during 2013 and 2015, the United States, Britain, Australia, Japan, and the countries that joined the European Union have a consistent level of inflation lower than Indonesia, the movement of SBI rate sufficient flutuaktif massively from 5.75% to 7.5% during the years 2013 to 2015, Indonesia public debt has increased significantly in 2013-2014 so that the government and people of Indonesia should encourage economic growth in a positive direction through a mix of monetary and fiscal policy expansionary appropriate expected.